Are Remittances a 'Catalyst' for Financial Access? Evidence from Mexico - Christian Ambrosius (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In policy discussions, it has frequently been claimed that migrants' remittances could function as a 'catalyst' for financial access among receiving households. This paper provides empirical evidence on this hypothesis from Mexico, a main receiver of remittances worldwide. Using the Mexican Family Life Survey panel (MxFLS) for 2002 and 2005, the results from the treatment-effect-model at household level show that a change in remittance status has an important impact on ownership of savings accounts and the availability of borrowing options. This effect is significant for rural, but not for urban households and important for microfinance institutions, but not for traditional banks.
Keywords: G21; O16; F24; 330; Remittances; Mexico; Financial Access; Microfinance